2021
DOI: 10.1111/tran.12479
|View full text |Cite
|
Sign up to set email alerts
|

The cultural politics of new Tibetan entrepreneurship in contemporary China: Valorisation and the question of neoliberalism

Abstract: Over the past decade, new forms of Tibetan entrepreneurship have emerged and proliferated in China, at the intersection of a national push for entrepreneurship in response to a slowing economy, the closure of non‐governmental organisations in Tibetan areas, declining state‐sector employment, and state concerns about stability. This paper explores the rise of these new Tibetan entrepreneurs in relation to two inter‐related concerns. First, it contributes to geographers’ calls for comparative studies of cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The rewards provided to the workers can raise their performance, dedication, and effectiveness. The study concluded that suitable and regular rewards increase workers' motivation to work harder and boost general performance (Yeh, 2022). The rewards provided to the workers can raise their performance, dedication and effectiveness.…”
Section: Introductionmentioning
confidence: 94%
“…The rewards provided to the workers can raise their performance, dedication, and effectiveness. The study concluded that suitable and regular rewards increase workers' motivation to work harder and boost general performance (Yeh, 2022). The rewards provided to the workers can raise their performance, dedication and effectiveness.…”
Section: Introductionmentioning
confidence: 94%
“…According to Yeh (2022) noted that micro and small business are the largest employer in China and make up more than 80 million and more than 40 million this number remain in the informal side. It likewise remains to use more each year at an average rate of around 2%.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…Her research participants repeatedly referred to the need to recover the idea of ‘living the good life’ ( mino bimaadiziwin ) which combines a concern with survival and wider affective and spiritual needs. This locally valued understanding of the good life includes, ‘The rebuilding of intense and spiritual relationships with family and land, the reclamation of ancestral territories, and the re‐envisioning, experimentation, and embodiment of alternative political economies’ (Daigle, 2015, p. 211, see also Chaves et al, 2018; Villalba, 2013; Yeh, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Marginalised people's quest for survival commonly may occur within a relatively circumscribed set of ‘local’ processes of managing different life spheres: acquiring food, shelter, work, education, healthcare, infrastructural support, and physical security. By contrast, the search for proper viability may play out within a wider milieu, such as a region (Oosterom et al, 2019) or nation (see Chatterji et al, 2019; Yeh, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation